IDENTIFIKASI JENIS ANNELIDA PADA HABITAT SUNGAI JANGKOK KOTA MATARAM - Nizar Azhari; Nofisulastri Nofisulastri (Bioscientist : Jurnal Ilmiah Biologi, 2018)
Jangkok River is one of the lotic ecosystems in the city of Mataram. Based on previous studies it was concluded that this river has various types of biodiversity in it. The purpose of this study was to identify the types of Annelida found in the Jangkok River in Mataram City. This type of research is descriptive exploratory research with quantitative and qualitative approaches. This research was conducted on March 14, 2018. The research samples were river water taken at 3 stations namely upstream, middle and downstream using purposive sampling technique. Based on its existence, the Annelida type was found in downstream stations as many as 46 individuals, and 5 at the middle station, whereas it was not found at the upstream station. The type of Annelida found is the Olygochaeta class with Lumbricus terestis species and Tubifex sp. and the Hirudinae class with Hirudo medicinalis species.